SISTEM PENDUKUNG KEPUTUSAN PENJUALAN KELAPA BULAT DI INDRAGIRI MENGGUNAKAN METODE WEIGTED PRODUCT (WP) - Firman; Rasyid Ridha, Muh. (JURNAL PERANGKAT LUNAK, 2021)
Decision Support System (DSS) is a system that can assist a person in making accurate decisions and targeted. Many problems can be solved by using CMS, one of which is a decision support system round oil sales. There are several methods that can be used in building a Weigted Produck SPK them. Weighted product method is one of several methods MADM (Multi attribute Decision Making). MADM method is a method of decision-making that is based on multiple attributes. This study uses a product weighted in determining the feasibility of a decision support system round oil sales.And there are some criteria on which to base decisions, among others, price, distance, trannfortasi. To create a new system that mengefesienkan time in processing the sales data, Provide an overview of a suitable price for oil where the coconut farmers will be marketed. This research is beneficial to coconut seller. As the clouds or the community is able to sell the coconut with high prices and minimal costs.